EfficientNet with transformer integrations for enhancing deepfake detections - Varsha, Saravanabavan (Nanyang Technological University, 2024)
The emergence of Artificial Intelligence has brought about significant advancements, yet it also raises concerns, notably regarding the proliferation of "deepfakes" – digitally altered facial media that blurs the line between reality and fabrication. Extensive research has been conducted to develop methods for detecting deepfakes, aiming to mitigate their adverse impacts.